The graveyard book - Gaiman, Neil.; McKean, Dave (New York : HarperCollins, 2008)
The orphan Bod, short for Nobody, is taken in by the inhabitants of a graveyard as a child of eighteen months and raised lovingly and carefully to the age of eighteen years by the community of ghosts and otherworldly creatures.
Wilson's Children, July 2009
School Library Journal, October 2008
Booklist starred, September 2008
Horn Book Starred, November 2008
Pub Weekly, September 2008
Kirkus Starred, August 2008
Keywords: Dead -- Juvenile fiction; Supernatural -- Juvenile fiction; Cemeteries -- Juvenile fiction; Dead -- Fiction; Supernatural -- Fiction; Cemeteries -- Fiction; Death -- Fiction; Supernatural -- Fiction; Cemeteries -- Fiction